Kekuatan Mengikat Who Patient Safety Rights Charter sebagai Instrumen Soft Law dalam Sistem Hukum Indonesia - Mohamad Ihsan Ramdani; Neni Ruhaeni; Ratna Sri Suminar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the binding force of the WHO Patient Safety Rights Charter (2024) as a soft law instrument within the Indonesian legal system and evaluates the potential application of its principles in the formulation of national health policies. The research employs a normative juridical method with descriptive, analytical, and comparative approaches toward international norms, including the International Covenant on Economic, Social and Cultural Rights (ICESCR) and the Global Patient Safety Action Plan (2021–2030), as well as relevant national regulations. The findings indicate that although the WHO Charter is not legally binding, it possesses substantial normative and moral authority derived from the ethical legitimacy of the World Health Organization and its alignment with the principles of the right to health. In Indonesia, several principles of the Charter have been partially reflected in Law No. 17 of 2023 on Health; however, normative gaps remain, particularly regarding patients’ participatory rights and medical justice. Soft law acquires its normative strength through moral legitimacy, broad acceptance, and integration into domestic policy frameworks. The study concludes that strengthening legal protection for patient safety in Indonesia requires the explicit incorporation of the WHO Charter’s principles into implementing regulations, thereby fostering a health law system that is equitable, accountable, and grounded in human rights.